Review of Neoperla (Plecoptera: Perlidae) from Zhejiang Province, China - Li, Weihai; Liang, Haiyan; Li, Wenliang (Zootaxa, 2013)
The species of the perlid genus Neoperla are reviewed from eastern coastal Zhejiang Province, China. Neoperla xuanson-gae sp. nov. is described and compared with related congeners. Neoperla yangae Du is considered a junior synonym of N. anjiensis Yang & Yang and the first record of N. flagellata Li & Murányi is given for the Province. Several additional species are redescribed or diagnosed. A provisional key to the known species for Zhejiang Province is also presented.